2005
DOI: 10.1016/j.bbalip.2005.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid utilisation and metabolism in caecal enterocytes of rainbow trout (Oncorhynchus mykiss) fed dietary fish or copepod oil

Abstract: A combined fatty acid metabolism assay was employed to determine fatty acid uptake and relative utilisation in enterocytes isolated from the pyloric caeca of rainbow trout. In addition, the effect of a diet high in long-chain monoenoic fatty alcohols present as wax esters in oil derived from Calanus finmarchicus, compared to a standard fish oil diet, on caecal enterocyte fatty acid metabolism was investigated. The diets were fed for 8 weeks before caecal enterocytes from each dietary group were isolated and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 50 publications
3
25
0
Order By: Relevance
“…This is supported by a study on fatty acid uptake by caecal enterocytes, which showed that esterification into cellular lipids was seen highest in 16:0 and C18 fatty acids. The overall utilization of fatty acids in phospholipid synthesis was seen low, but highest with 16:0 (Oxley et al, 2005). Dietary essential fatty acids have been shown to be important in mucosal defense and restitution.…”
Section: Discussionmentioning
confidence: 95%
“…This is supported by a study on fatty acid uptake by caecal enterocytes, which showed that esterification into cellular lipids was seen highest in 16:0 and C18 fatty acids. The overall utilization of fatty acids in phospholipid synthesis was seen low, but highest with 16:0 (Oxley et al, 2005). Dietary essential fatty acids have been shown to be important in mucosal defense and restitution.…”
Section: Discussionmentioning
confidence: 95%
“…With the importance of lipid as an energy source in most fish species, particularly salmonids and marine fish, there have been several studies on fatty acid oxidation in fish (Crockett and Sidell 1993;Kiessling and Kiessling 1993;Frøyland et al 1998Frøyland et al , 2000Fjermestad et al 2000;Torstensen et al 2000;Nanton et al 2003;Vegusdal et al 2004;Oxley et al 2005;Stubhaug et al 2005aStubhaug et al ,b,c, 2006.…”
Section: Discussionmentioning
confidence: 99%
“…This is based on studies measuring β-oxidation capacity using subcellular fractions, in which long-chain monenes were preferred over PUFA as substrates in fish (Henderson and Sargent 1985;Kiessling and Kiessling 1993;Henderson 1996;Frøyland et al 2000). However, recent intact cell studies, which measure relative fates of fatty acids taken up by the cells, have suggested that PUFA can be relatively more oxidized than 18:1n-9 in salmonid hepatocytes or enterocytes (Oxley et al 2005;Stubhaug et al 2005c). In contrast, in the trial with salmon postsmolts mentioned above, there was a tendency for β-oxidation in liver in salmon fed VOs to be higher than in fish fed FO in the autumn after transfer, but by the following spring there was no difference in β-oxidation capacity in liver between fish fed FO or VO (Stubhaug et al 2005a).…”
Section: Discussionmentioning
confidence: 99%
“…The lipid and fatty acid composition of the intestinal cells can be significantly modified by the dietary lipid and fatty acid composition (Caballero et al. 2003; Oxley et al. 2005a; Ruyter et al.…”
Section: The Effects Of Fish Oil Replacement On Feed Qualitymentioning
confidence: 99%